Implementasi Akuntansi Kombinasi Bisnis Sesudah Penerapan PSAK 22 dan Konvergensi IFRS pada PT Telekomunikasi Indonesia - Adelia Furry Avriandi; Apriana Nur Asyifa; Sandra Audina Maharani; Endang Kartini Panggiarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
. This research was conducted to provide in-depth insight into how PT Telecom Indonesia manages implementation of IFRS 22 and IFRS convergence in the context of business combination accounting. Adoption of PSAK 22, business combinations recorded using the acquisition method. The transferred remuneration is calculated on the basis of its fair value, which is the difference between the fair value of the transferred asset, the assumed liability, and the equity instrument granted to the acquired party in exchange for control. The combination of business and IFRS convergence has a correlation because it improves the effectiveness of information in the financial statements of PT Telekomunikasi Indonesia Tbk. This research uses the method of literature review or literature reviews to obtain research material. . This research was conducted to provide in-depth insight into how PT Telecom Indonesia manages implementation of IFRS 22 and IFRS convergence in the context of business combination accounting. Adoption of PSAK 22, business combinations recorded using the acquisition method. The transferred remuneration is calculated on the basis of its fair value, which is the difference between the fair value of the transferred asset, the assumed liability, and the equity instrument granted to the acquired party in exchange for control. The combination of business and IFRS convergence has a correlation because it improves the effectiveness of information in the financial statements of PT Telekomunikasi Indonesia Tbk. This research uses the method of literature review or literature reviews to obtain research material.